2017
DOI: 10.1016/j.jneb.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a WIC-Based Intervention to Promote Exclusive Breastfeeding: Challenges, Facilitators, and Adaptive Strategies

Abstract: Implementation was shaped by clinic setting and adaptive strategies. Future WIC interventions may benefit from formal consideration of intervention fit with local clinic setting and allowable adaptations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…3 In addition, studies indicated that provision of BF support within WIC settings may vary by race/ethnicity, and that black women were less likely to be offered lactation support. 25,26 In this study, it was likely that adherence to the study protocol and perceived improvements in staff BF counseling competencies and confidence through learning community training, as reported by participating WIC staff at the end of the intervention, 15 may have led to enhanced opportunities for all participants (in particular non-white women) to receive tailored BF support. On the other hand, the observation of little or no effect among white women, who had a relatively high prevalence of exclusive BF, suggested the potential of a ceiling effect, which can restrict and/or conceal the potential effectiveness of an intervention.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…3 In addition, studies indicated that provision of BF support within WIC settings may vary by race/ethnicity, and that black women were less likely to be offered lactation support. 25,26 In this study, it was likely that adherence to the study protocol and perceived improvements in staff BF counseling competencies and confidence through learning community training, as reported by participating WIC staff at the end of the intervention, 15 may have led to enhanced opportunities for all participants (in particular non-white women) to receive tailored BF support. On the other hand, the observation of little or no effect among white women, who had a relatively high prevalence of exclusive BF, suggested the potential of a ceiling effect, which can restrict and/or conceal the potential effectiveness of an intervention.…”
Section: Discussionmentioning
confidence: 94%
“…12 Although a priority of the NYS WIC program is to promote and support BF, this intervention may have been particularly effective in part because the YCDI intervention protocol increased the intensity of BF promotion: for example, by prioritizing BF counseling at each of 3 prenatal WIC visits and concentrating efforts on providing BF support to postpartum women within the first few days immediately after birth. Similarly, it is possible that striving for nutritionist and PC continuity across visits improved rapport between WIC staff and participants, thus supporting continuity of care 15 and improving exclusive BF outcomes. 21 Examination of BF outcomes by race and ethnicity revealed that the impact of the intervention was most profound among black and Hispanic women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manfaat kesehatan dari menyusui semakin meningkat ketika pemberian ASI eksklusif dipertahankan selama enam bulan (Charlick, McKellar, Gordon, & Pincombe, 2018;Darwent & Kempenaar, 2014;Eldridge, Hartnett, Lee, Sekhobo, & Edmunds, 2017;S., A.P., & V., 2018;Sriraman, 2017). ASI eksklusif didefinisikan sebagai pemberian ASI saja (termasuk ASI dan obat-obatan) dan tidak termasuk susu buatan bayi, susu nonmanusia, air atau minuman berbasis air, teh atau jus buah (Charlick et al, 2018;De Jager, Broadbent, Fuller-Tyszkiewicz, & Skouteris, 2014).…”
Section: Pendahuluanunclassified
“…[9][10][11] In addition to direct interventions, organizational and staff changes were implemented. [12][13][14] These coordinated strategies reflect the sociological framework upon which WIC operates, while facilitating independent efforts by local and state agencies.…”
mentioning
confidence: 99%